The Role of Capital Markets in Indonesia's Domestic Investment Financing - Sutanto, Angeline; Cassidy, Felice; Fellin, Fellin; Kwok, Kelly; Chua, Melisa; Pendapotan, Yovin; Sitorus, Rolib (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research conducted aims to determine the role of the capital market in supporting investment financing in Indonesia and its impact on national economic growth, and to determine the relationship between the capital market in providing investment financing and its impact on the dynamics of the Indonesian economy globally. The research method uses library research, where the process of searching, collecting, and analyzing data comes from various library sources, such as books, journals, and electronic databases. Topic identification, source finding, information assessment, data collection, analysis, and writing are part of the process. The expected outcome is that the capital market is the main source of financing for many large projects in Indonesia. Projects such as infrastructure, technology, energy, and manufacturing often require huge amounts of capital. The capital market serves as a platform that connects the funding needs of companies with investors from within and outside the country.